Acetylsalicylic acid dosed at bedtime vs. dosed in the morning for circadian rhythm of blood pressure- a systematic review and meta-analysis - Nadeem, Abdullah; Rais, Taruba; Aamir, Minahil; Habte, Alexander; Siddiqui, Tasmiyah; Karamat, Riyan Imtiaz; Munsab, Rabbia; Habib, Ashna (Frontiers in Cardiovascular Medicine, 2024)
Cardiovascular disease (CVD) is a leading global cause of morbidity and mortality, with high systolic blood pressure (SBP) identified as a major risk factor. Aspirin (Acetylsalicylic acid -ASA) has been considered for CVD prevention, prompting questions about its optimal use in primary and secondary prevention and the ideal dosing time to maximize its impact on circadian blood pressure rhythms. Previous research suggests a potential benefit of bedtime aspirin dosing in reducing blood pressure, attributed to its effects on the renin-angiotensin-aldosterone system and nitric oxide production. This systematic review and meta-analysis aim to further explore the circadian effects of aspirin on blood pressure, focusing on the timing of administration. Adhering to PRISMA guidelines, a comprehensive search of PubMed, Cochrane Library, and clinicaltrials.gov was conducted. Randomized controlled trials (RCTs) involving patients aged >18 with cardiovascular history and hypertension were included. The primary objective was to assess the impact of bedtime-dosed and morning-dosed aspirin on systolic and diastolic blood pressure. Low-dose aspirin was administered for primary or secondary prevention. The Cochrane Risk of Bias tool evaluated study quality. Meta-analyses were conducted using RevMan 5.3, with mean deviations and 95% confidence intervals employed for outcomes. Initial searches yielded 1,181 articles, with six studies meeting the inclusion criteria. These RCTs involved 1,470 patients, with 1,086 completing follow-up. Bedtime aspirin dosing demonstrated a significant reduction in both systolic and diastolic blood pressure compared to morning dosing (p < 0.05). Meta-analysis results for systolic blood pressure revealed a weighted mean difference of approximately 3.65 mmHg in favor of bedtime dosing, with low heterogeneity (I2 = 0%). For diastolic blood pressure, the weighted mean difference was 1.92, again favoring bedtime dosing, with 3% heterogeneity. This meta-analysis, involving over 1300 cardiovascular/hypertensive patients, supports the effectiveness of bedtime aspirin in reducing systolic and diastolic blood pressure compared to morning dosing. The results align with previous findings but distinguish themselves by incorporating a more diverse patient population and addressing moderate heterogeneity. While the study's outcomes are promising, further research, including larger sample sizes and longer durations, is warranted for comprehensive clinical implementation.